The Impact of Corruption on Structural Poverty in Indonesia - Aliya Nabila Nisriina; Ida Bagus Putu Purbadharmaja (International Journal of Economics Accounting and Management, 2026)
This research employs a quantitative approach using panel data regression analysis across selected Indonesian provinces during the period 2014 to 2024. The dependent variable is structural poverty, measured through composite indicators reflecting chronic poverty, exclusion from basic services, and intergenerational deprivation. Independent variables include corruption in public procurement, effectiveness of supervisory institutions, and inequality in social budget allocation. Data are obtained from secondary sources, including Statistics Indonesia (BPS), the Corruption Eradication Commission (KPK), Indonesia Corruption Watch (ICW), and Transparency International. The results are expected to demonstrate that corruption in public procurement and unequal social budget allocation significantly increase structural poverty, while weak effectiveness of supervisory institutions exacerbates governance failures that sustain poverty traps. This study contributes empirically to the literature by integrating governance and poverty indicators within a panel data framework. The findings are expected to provide policy relevant insights for strengthening institutional oversight, improving transparency in public spending, and designing more equitable and effective poverty reduction strategies in Indonesia